2001
DOI: 10.1038/90415
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The translationally controlled tumor-associated proteins (TCTPs) are a highly conserved and abundantly expressed family of eukaryotic proteins that are implicated in both cell growth and the human acute allergic response but whose intracellular biochemical function has remained elusive. We report here the solution structure of the TCTP from Schizosaccharomyces pombe, which, on the basis of sequence homology, defines the fold of the entire family. We show that TCTPs form a structural superfamily with the Mss4/D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(63 citation statements)
references
References 24 publications
1
62
0
Order By: Relevance
“…In accordance, polo-like kinase was shown to interact directly with and phosphorylate TCTP, further implicating TCTP in cell cycle-related activities (14). More recently, NMR analysis revealed that TCTP has a structural homology with the mammalian suppressor of Sec4 (MSS4/DSS4), a protein that functions as a guanine nucleotide-free chaperone (15). In line with these findings, we recently identified a guanine nucle-* The costs of publication of this article were defrayed in part by the payment of page charges.…”
Section: Tsap6mentioning
confidence: 88%
“…In accordance, polo-like kinase was shown to interact directly with and phosphorylate TCTP, further implicating TCTP in cell cycle-related activities (14). More recently, NMR analysis revealed that TCTP has a structural homology with the mammalian suppressor of Sec4 (MSS4/DSS4), a protein that functions as a guanine nucleotide-free chaperone (15). In line with these findings, we recently identified a guanine nucle-* The costs of publication of this article were defrayed in part by the payment of page charges.…”
Section: Tsap6mentioning
confidence: 88%
“…The predicted 3D structure of this protein is quite similar to that of the canonical member of this family, from Schizosaccharomyces pombe, and to that predicted for most members of this family. 4,24 In general, the predicted structure of CmTCTP displays domains for tubulin and calcium binding, as well as a TCTP2, but not TCTP1, signature, among others. Thus, CmTCTP biochemical activity may be similar to mammalian and insect (Drosophila) TCTP.…”
Section: Resultsmentioning
confidence: 99%
“…Chinese hamster ovary (CHO) cells were grown as described previously (43) in Dulbecco's modified Eagle's medium/Nutrient Mixture Ham's F-12 (Sigma) supplemented with 9% (v/v) fetal bovine serum, 100 g/ml streptomycin sulfate, and 100 units/ml penicillin G at 34°C. The tsH1 line was derived by Thompson et al (34) and contains a temperature-sensitive leucyl-tRNA synthetase that is active at 34°C but defective at 39.5°C.…”
Section: Methodsmentioning
confidence: 99%